Profile of the physical condition of the determinant of the serve and skills on the court tennis service - Ali, Muhammad; Supriono, Slamet; Turiyem; Syarifah (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of this study was to find out the determinant physical condition and service skills of court tennis in tennis players of the city's achievement coaching club Jambi. The subjects of this study were 15 tennis players of the city's achievement coaching club Jambi. Test instruments Push-Up Test (arm muscle strength), Sit and Reach (flexibility), Tennis ball throwing test (Eye and Hand Coordination), and Service Test (Service Skills). The results showed that the results of arm muscle strength owned by players coaching the achievements of the city of Jambi's tennis court most of the 14 players gained a good category once with a percentage of 93%. The togok flexibility test that players coaching the achievements of the city of Jambi city tennis mostly 9 players gained a very good category with a percentage of 60%. The eye and hand coordination tests that Jambi city court tennis coaching players have most of the 12 players gained a good category with a percentage of 80%.0%. And the court tennis service that the Jambi city court tennis coaching players have mostly 10 players gained less category with a percentage of 67%.